UPAYA PENINGKATAN KEMAMPUAN MENULIS KATA SEDERHANA MELALUI METODE LATIHAN SISWA KELAS I SD NEGERI 014 PAGARAN TAPAH DARUSSALAM - Rosmin Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by the lack of ability to write simple words first grade students of SD Negeri 014 Pagaran Tapah Darussalam Rokan Hulu. This study aims to improve the ability to write simple words first grade students of SD Negeri 014 Pagaran Tapah Darussalam, held for 1 month. The subjects were students of class I SD Negeri 014 Pagaran Tapah Darussalam academic year 2015/2016 the number of students as many as 7 people, consisting of 5 boys and 2 girls. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the results of the study it can be concluded that the ability to write simple words can be enhanced through training methods first grade students of SD Negeri 014 Pagaran Tapah Darussalam. This statement can be accepted, because the students' ability to write simple words increased. Where known from preliminary data the average value of 59.3 or in the medium category. When viewed from the classical completeness, there is 28.6% or 2 students who completed gain value according to standards KKM, which is a minimum of 65. However, after the implementation of training methods, obtained an average value of 67.1 or higher in a category. When viewed from the classical completeness has reached 57.1%, or 4 students, but research has not been successful. Because this study was successful when 85% of students obtaining a minimum value of 65. While on the second cycle, to reach an average value of 80.7 or higher in a category. When viewed from the classical completeness, has acquired all of the students (100%). Thus, the researchers limited the study to the second cycle. Because of the results obtained was clear, that improve the students' first-class students of SD Negeri 014 Pagaran Tapah Darussalam in writing simple words.